2015
DOI: 10.5152/jtgga.2015.0134
|View full text |Cite
|
Sign up to set email alerts
|

Changing perspectives of infectious causes of maternal mortality

Abstract: Objective: Infections significantly contribute to maternal mortality. There is a perceived change in the spectrum of such infections. This study aims to estimate the contribution of various types of infections to maternal mortality. Material and Methods:We retrospectively reviewed records of maternal death cases that took place between 2003 and 2012 in the Christian Medical College, Vellore, India. The International Classification of Diseases-Maternal Mortality was used to classify the causes of deaths and Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
3
9
0
2
Order By: Relevance
“…7,9 Halder et al reported the causes of maternal deaths that had signs of severe systemic infection. 18 It is seen that the causes found in the present study was directly or indirectly related to maternal mortality which coincides with many studies across India. Studies have found that haemorrhage, sepsis, eclampsia and obstructed labour account for 80% of all maternal deaths worldwide.…”
Section: Discussionsupporting
confidence: 91%
“…7,9 Halder et al reported the causes of maternal deaths that had signs of severe systemic infection. 18 It is seen that the causes found in the present study was directly or indirectly related to maternal mortality which coincides with many studies across India. Studies have found that haemorrhage, sepsis, eclampsia and obstructed labour account for 80% of all maternal deaths worldwide.…”
Section: Discussionsupporting
confidence: 91%
“…Majority of the pregnant women believed that infection can cause maternal death. This agrees with the indings of Halder, Vijayselvi & Jose [34]. Hypertensive disorders of pregnancy are one of the most common direct causes of maternal mortality [35][36][37][38][39].…”
Section: Causes Of Maternal Mortalitysupporting
confidence: 89%
“…Adanya komplikasi masa nifas terutama infeksi dapat menyebabkan kematian maternal akibat menyebarnya kuman ke dalam aliran darah (septikemia), perdarahan pada masa nifas dapat berlanjut pada terjadinya kematian maternal terutama bila ibu tidak segera mendapat perawatan awal untuk mengendalikan perdarahan. 7 Hasil analisis statistik menunjukkan pengaruh antara paritas dengan kematian maternal (OR = 0,035; 95% CI : 0,004 -0,300; p = 0,000). Hasil penelitian ini sesuai dengan Penelitian Kozuki et al bahwa paritas dan usia ibu telah terbukti dapat meningkatkan risiko prematuritas, dan kematian.…”
Section: Pendahuluanunclassified